(untitled) (Physical Education, Health and Social Sciences, 2025)
Background CISC is a valuable procedure for survivors of Spinal Cord Injury to use in managing urinary incontinence, which can cause complications like reinfection by Urinary Tract Infections and problems with the bladder. Nevertheless, many patients with an SCI are still challenged to master CISC; hence, it is essential to identify adequate training strategies. Aim The purpose of this research was to assess the effectiveness of using skill demonstration on the overall effectiveness of CISC in increasing technical proficiency, assertiveness, and self-sufficiency among SCI survivors. Methods Quasi-experimental research was used in this study, which was carried out at the Paraplegic Centre Hayatabad Peshawar with a sample of 54 participants selected through a convenient sampling technique. Information was obtained with a translated and cross-culturally adapted 12-item checklist of CISC performance that evaluated the performance before and after an intervention with the teaching of hands-on skills. To compare the pre and post-experimental data, the results of the paired sample t-tests and the Chi-square test were obtained to check the efficacy of the behavioral intervention. Results The results showed a positive shift in mean practice scores from pre-intervention (70.25%) to post-intervention (94.52%) in CISC skills, Wilcoxon test p < 0.0001. Concerning the intervention proposal, there was a significant improvement in good practice, with the number rising from 18.5% pre-intervention to 74.1% post-intervention. While receptiveness to change was influenced by education level and previous training in CISC, age and marital status did not impact the results. Conclusion Implementation of skills has demonstrated a positive impact on improving the CISC among SCI survivors and controlling complications. These results indicate the need to include practical cases in the training methods used to teach SCIs to become more self-sufficient in their everyday lives.